Improving Social Studies Learning Outcomes Through Group Investigation Learning Model Assisted with Audio-Visual Media - Octaviyantari, Ni Luh Ardhia; Suarni, Ni Ketut; Widiana, I Wayan (Journal of Education Technology, 2020)
The less optimal student learning outcomes due to underactive students and the deficient of variations in the use of models and learning media is one of the reasons this research was conducted. The purpose of this research is to analyze the impact of the group investigation model assisted by audiovisual media on social studies learning outcomes of five-grade elementary school students. This research was a quasi-experimental research with a non-equivalent post-test only control group design. The population in this research was the five graders contained 129 students. Taking samples for research used a sample random sampling technique. The sample of this research were 35 students for an experimental class and 35 students for a control class. Data collection methods used were test methods with multiple-choice test forms that have been validated. Data collected were analyzed by descriptive statistical analysis and inferential statistical analysis using the t-test formula. The results of this research indicate that there are differences in social studies learning outcomes between students who were taught using the group investigation model-assisted audiovisual media and students using the conventional learning model. This is indicated by the value of t-count > t-table (3,781 > 2,000) with a significance level of 5%. So H1 is accepted. Besides, the average score of student’s social studies learning outcomes in experimental class >  average score of student’s social studies learning outcome in control class (23,71>21,29). This model can be used for teachers in creating fun learning so that they can make a good contribution to learning activities.